On Some Discrepancies between Rashi's Commentary on the Talmud and His Commentary on the Bible - Himmelfarb, Lea (Hebrew Union College annual, 2004)
Various explanations have been offered as to why Rashi offers different interpretations of the same matter in his commentaries on the Talmud and the Bible. We suggest that Rashi provides an interpretation in his Bible commentary that is contrary to the one given in his commentary on the Talmud because the former is consistent with the interpretive aspect implicit from the Masorah notes, that he regarded as authoritative. The purpose of the Masorah is to accurately preserve the biblical text and its wording, and it is primarily interested in exceptional and rare phenomena. Although the Masorah notes relate to textual issues, Rashi ascribes them interpretive significance as well. The current study presents three examples in which the differences between Rashi's Talmud and Bible commentaries may be explained by a singular element, namely, the Masorah. The essay compares Rashi's differing interpretations of the same verse in his Talmud and Bible commentaries, and indicates the Masorah note on which, or on the likes of which, Rashi relied in his commentary on the Bible.